THE IMPLEMENTATION OF PERSONALITY DEVELOPMENT PROGRAMS IN REDUCING SUICIDE RISK AMONG JUVENILE INMATES AT THE SPECIAL DEVELOPMENT INSTITUTION FOR CHILDREN CLASS II BANDAR LAMPUNG - Dicaprio, Fedro; Biafri, Vivi Silviani (Journal of Management Small and Medium Enterprises (SMEs), 2025)
This study aims to analyze the implementation and impact of the personality development program at the Special Development Institution for Children Class II Bandar Lampung in reducing the suicide risk among juvenile inmates. This research employs a qualitative method with data collection techniques such as interviews, observations, and document analysis. The research informants include LPKA officers and juvenile inmates at risk of suicide. The study results indicate that the personality development program Salam Pemasyarakatan (Salampas) and religious programs play an essential role in preventing the suicide risk among juvenile inmates. The implementation of this program focuses on emotional and spiritual guidance, routinely provided by officers and religious instructors. However, shortcomings were identified in the form of insufficient control and a lack of psychological experts to support the mental health of the juvenile inmates. The proposed solution is the Sehat Mental Anak Binaan (Semabi), which includes mental health screening and counseling activities for the inmates. This research recommends greater involvement of psychological experts and stricter control to ensure the sustainability of the program. Keywords: Personality Development; Suicide; Juvenile Inmates; LPKA; Mental Health